The Cranial Osteology and Feeding Ecology of the Metriorhynchid Crocodylomorph Genera Dakosaurus and Plesiosuchus from the Late Jurassic of Europe - Young, Mark T.; Brusatte, Stephen L.; Brandalise de Andrade, Marco; Desojo, Julia Brenda; Beatty, Braian L.; Steel, Lorna; Fernández, Marta Susana; Sakamoto, Manabu; Ruiz Omeñaca, José Ignacio; Schoch, Rainer (PLoS ONE)
Background: Dakosaurus and Plesiosuchus are characteristic genera of aquatic, large-bodied, macrophagous metriorhynchid crocodylomorphs. Recent studies show that these genera were apex predators in marine ecosystems during the latter part of the Late Jurassic, with robust skulls and strong bite forces optimized for feeding on large prey. Methodology/Principal Findings: Here we present comprehensive osteological descriptions and systematic revisions of the type species of both genera, and in doing so we resurrect the genus Plesiosuchus for the species Dakosaurus manselii. Both species are diagnosed with numerous autapomorphies. Dakosaurus maximus has premaxillary 'lateral plates'; strongly ornamented maxillae; macroziphodont dentition; tightly fitting tooth-to-tooth occlusion; and extensive macrowear on the mesial and distal margins. Plesiosuchus manselii is distinct in having: non-amblygnathous rostrum; long mandibular symphysis; microziphodont teeth; tooth-crown apices that lack spalled surfaces or breaks; and no evidence for occlusal wear facets. Our phylogenetic analysis finds Dakosaurus maximus to be the sister taxon of the South American Dakosaurus andiniensis, and Plesiosuchus manselii in a polytomy at the base of Geosaurini (the subclade of macrophagous metriorhynchids that includes Dakosaurus, Geosaurus and Torvoneustes). Conclusions/Significance: The sympatry of Dakosaurus and Plesiosuchus is curiously similar to North Atlantic killer whales, which have one larger 'type' that lacks tooth-crown breakage being sympatric with a smaller 'type' that has extensive crown breakage. Assuming this morphofunctional complex is indicative of diet, then Plesiosuchus would be a specialist feeding on other marine reptiles while Dakosaurus would be a generalist and possible suction-feeder. This hypothesis is supported by Plesiosuchus manselii having a very large optimum gape (gape at which multiple teeth come into contact with a prey-item), while Dakosaurus maximus possesses craniomandibular characteristics observed in ...